2014
DOI: 10.1161/jaha.114.001277
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged PR Interval Predicts Clinical Recurrence of Atrial Fibrillation After Catheter Ablation

Abstract: BackgroundA prolonged PR interval is known to be a poor prognostic factor in cardiovascular disease. The aim of this study was to investigate the association between PR interval and clinical outcome in patients undergoing radiofrequency catheter ablation (RFCA) of atrial fibrillation (AF).Methods and ResultsWe prospectively included 576 patients with AF (75.5% male, 57.8±11.6 years old, 68.8% paroxysmal AF) who underwent RFCA. We analyzed preprocedural sinus rhythm ECGs obtained in the absence of antiarrhythmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…PR interval prolongation in turn has been linked with advanced atrial remodeling and worse ablation outcome [26]. …”
Section: Discussionmentioning
confidence: 99%
“…PR interval prolongation in turn has been linked with advanced atrial remodeling and worse ablation outcome [26]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies regarding the relationship of prolonged atrial mechanical delay with non-dipper prehypertension, 12 obesity, 13 mitral annulus calcification, 14 and connective tissue diseases. [23][24][25] Deniz et al 26 demonstrated that intra-left atrial mechanical delay was an independent risk factor for PAF when the cut-off point was 25 ms, with a sensitivity of 79% and a specificity of 66%. 22 In addition, previous studies have shown that patients with AF exhibited increased atrial mechanical delay, especially in patients with AF recurrence.…”
Section: Association Between Atrial Mechanical Delay and Cardiac DImentioning
confidence: 99%
“…22 In addition, previous studies have shown that patients with AF exhibited increased atrial mechanical delay, especially in patients with AF recurrence. [23][24][25] Deniz et al 26 demonstrated that intra-left atrial mechanical delay was an independent risk factor for PAF when the cut-off point was 25 ms, with a sensitivity of 79% and a specificity of 66%.…”
Section: Association Between Atrial Mechanical Delay and Cardiac DImentioning
confidence: 99%
“…P wave analysis using standard surface 12-lead electrocardiography (ECG) is a simple and cost-effective modality for determining the prognosis of AF. We recently reported that low P wave amplitude in lead I with displaced interatrial conduction, 7 and prolonged PR interval, 8 are associated with a higher clinical recurrence rate of AF after catheter ablation.…”
Section: Introductionmentioning
confidence: 98%